Analysis of NLR, PLR, and Carcinoembryonic Antigen in Colorectal Cancer Patients - Parabang, Budi; Esa, Tenri; Bahrun, Uleng (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Colorectal cancer (CRC) is the second leading cause of cancer death worldwide. The development and prognosis of CRC are affected by the tumor's appearance and the host's inflammatory response. A combination of several parameters, including the Neutrophil-Lymphocyte Ratio (NLR) and Platelet-Lymphocyte Ratio (PLR), has been used as a cancer prognostic marker. Research needs to be performed to analyze its role in CRC. This study aimed to determine the differences in the NLR, PLR, and CEA values with the severity and site of CRC. Medical record data were collected from 246 CRC patients from January 2021 to June 2022 at Dr. Wahidin Sudirohusodo Hospital were used and grouped by severity (metastatic and non-metastatic) and site (left colon, right colon, rectum). This study collected the data on NLR, PLR, and CEA levels. The Mann-Whitney, Spearman Rho, and Kruskal-Wallis tests were used for statistical analysis by the research objectives (significant if p<0.05). There were differences in median PLR (194.47 vs. 201.18; p=0.045) and CEA (3.3 ng/mL vs. 11.95 ng/mL; p<0.001) between the metastatic and non-metastatic groups, whereas there was no significant difference of median NLR between the two groups (2.77 vs. 2.79; p=0.438). No correlation was found between the NLR, PLR, and CEA level values with the location of CRC (p-values 0.978, 0.511,  0.419, respectively). PLR and CEA values were higher in metastatic CRC than in non-metastatic CRC, while NLR value was not significantly different. There was no correlation between the NLR, PLR, and CEA level values with the CRC site.